Gray Matter Volume Changes in the Apathetic Elderly - Yan, Hongjie; Onoda, Keiichi; Yamaguchi, Shuhei (Frontiers in Human Neuroscience, 2015)
This study is to test the hypothesis that apathy in healthy participants is closely related to the prefrontal-basal ganglia circuit and associated structural changes. We selected 36 healthy aged participants with (n = 18) or without apathy (n = 18) from our database. Participants underwent structural MRI scanning, providing data for voxel based morphometric analysis to explore gray matter changes associated with apathy. Compared to the non-apathy group, the apathy group showed reduced gray matter volume of the right putamen, whereas volumes of the bilateral inferior frontal gyri and left inferior occipital gyrus showed increase. When depression scores were included in a regression model as a covariate, apathetic participants showed decreased gray matter volume in the right precentral gyrus compared to the non-apathetic participants. These findings suggest that apathy is associated with the gray matter volume in the prefrontal-basal ganglia network, and may have a neuroanatomical basis distinct from depression in healthy elderly.